Bryophyta di Sekitar Kawasan Bandar Udara Internasional Syamsudin Noor Kalimantan Selatan: Bryophyta in the vicinity of Syamsudin Noor International Airport, South Kalimantan - Riyana, Yuninda; Gendro Sari, Sasi; Gunawan, Gunawan (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2020)
The diversity of mosses around the Syamsudin Noor international airport was never reported. This study aimed to reveal the variety of moss around the Syamsudin Noor International Airport area. This research uses the purposive sampling method. Measurement of environmental parameters includes air temperature, light intensity, humidity, and soil pH. Moss identification refers to the book A Handbook of Malesian Mosses volume 1 Sphagnales to Dicranales and A Handbook of Malesian Mosses volume 2 Leucobryaceae to Buxbaumiaceae. The moss morphological characters observed included the leaves, stems, and rhizoids using a stereomicroscope. The results showed that in Syamsudin Noor International Airport's vicinity, there are as many as five types of moss consisting: Pseudoracelopus acaulis, Hyophila apiculata Homalothecium lutescens, Ectropothecium falciforme, Fissidens atroviridis. The most dominant type of moss is Pseudoracelopus acaulis. The range of environmental parameter values ??is air temperature 28-34oC, light intensity 20-35 lux, humidity 74-84%, and soil pH 7. This study's results are preliminary data to determine the environmental change around Syamsudin Noor International Airport.